Bali Tourism Discursive Strategies in “Balilivin” Instagram Account - Pratistita, Ni Wayan Ita; Ayomi, Putu Nur; Maharani, Putu Devi; Tustiawati, Ida Ayu Mela (Humanis; Vol 26 No 4 (2022)DO - 10.24843/JH.2022.v26.i04.p06, 2022)
Today's popularity of a tourist destination is often supported by its existence on social media. Engaging narratives and pictures influence visitor interest in traveling to an area. This study aims to see the discourse strategy used by a highly followed Instagram account @balilivin in promoting tourist attractions in Bali using the theory of Wodak & Meyer (2001). The data was collected in January 2022. Using descriptive-qualitative method, t he study found that most posts divide human social actors into visitors and locals. Bali as a destination and its people is described with a highly positive image with bombastic words. Pictures and captions framed Bali as an ideal paradise apart from various realities unshown on social media.